Soy isoflavone effects on the adrenal glands of orchidectomized adult male rats: a comprehensive histological and hormonal study - Milošević, Verica Lj; Severs, Walter B; Ristić, Nataša M; Manojlović-Stojanoski, Milica N; Popovska-Perčinić, Florina V; Šošić-Jurjević, Branka T; Pendovski, Lazo B; Trifunović, Svetlana L; Miler, Marko Š; Ajdžanović, Vladimir Z (My University, 2018)
Genistein (G) and related soy phytoestrogens have been studied for potential usefulness in different chronic diseases, and may ameliorate signs of aging. They have a profound influence on the hypothalamo-pituitary-adrenal (HPA) axis. The present study utilized the rat model of mild andropause to thoroughly evaluate the effects of G and soy extract on the adrenal gland and related blood hormones. Adult male rats were orchidectomized (Orx) or sham operated (SO). Orx rats received daily subcutaneous injections for 3 weeks of solvent, or G (Orx+G, 30 mg/kg), or commercial soy extract (Orx+Soy, 30 mg/kg). Adrenal glands and blood were harvested at the end of the treatment for hormone analyses, histology and design-based stereology. Compared to SO rats Orx evoked significant (P<0.05) changes including: the replicating cell number in the 3 adrenocortical zones; vascularity and cortical volume and blood levels of adrenocorticotropic hormone (ACTH), aldosterone and dehydroepiandrosterone (DHEA). When comparing Orx vs. Orx+G groups the following significant (P<0.05) changes were observed: a further increase in number of replicating cells in zonas glomerulosa and reticularis, vasculature network presence, cortical and zona reticularis volumes, ACTH and corticosterone concentrations, and lower DHEA levels. Comparing Orx vs. Orx+Soy resulted in elevated (P<0.05) ACTH and corticosterone levels. Structural integrity of the adrenal gland was unchanged vs. SO rats. Overall, G and soy extract treatments resulted in proliferative activity and/or vasculature support in the adrenal cortex. The data and current literature support the impression of a beneficial effect of soy components on the homeostatic response to stress.